Who consumes whole grains, and how much? - Lang, R; Jebb, SA (2003)
Regular consumption of whole grain foods has been associated with a reduction in the incidence of cardiovascular disease and diabetes, reductions in cancer mortality at certain sites and an overall reduction in premature death. Although benefits are observed at relatively low levels of intake (between two and three servings per d), the consumption of whole grain foods in some Western countries is less than one serving per d. The main sources of whole grain are wholemeal and rye breads and whole grain breakfast cereals. Typical consumers of wholegrain foods tend to be older, from a high socio-economic group, are less likely to smoke and are more likely to exercise than non-consumers. Some of these attributes may contribute to the observed health benefits. However whole grain foods are an important source of a range of nutrients as part of a healthy eating plan. There is considerable scope for strategies to promote increased consumption of whole grain foods to reduce the risk of a variety of chronic diseases.